The complete mitochondrial genome of a mangrove plant: Bruguiera sexangula - Jingwen Zhang; He Bai; Ying Zhang (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of mangrove plant Bruguiera sexangula was analyzed in this paper, which is the first for the genus within the family Rhizophoraceae. The mitogenome sequence is 303,026 bp in length containing 3 ribosomal RNA genes, 20 transfer RNA genes, and 37 protein-coding genes. Genes ccmFc, rps3, and cox2 contain one intron each, genes nad1 and nad5 contain two introns each, gene nad4 contains three introns and gene nad2 and nad7 contain four introns each. Gene nad1, nad2, and nad5 are trans-splicing genes. Phylogenetic analysis using the maximum-likelihood method positioned B. sexangula closely with Citrus sinensis.